Validitas Validitas dan Praktikalitas E-Modul Interaktif Asam Basa Berbasis Problem Based Learning Terintegrasi Canva - Ari Andesta Mirwandi; Syamsi Aini (Postgraduate, University of Mataram, 2025)
This study aims to produce an interactive e-module of acid-base based on Problem Based Learning (PBL) integrated with Canva and analyze the validity and practicality of the developed e-module. The type of research used is Research and Development (R&D) with a 4D development model. The 4D development model consists of 4 stages, namely the define, design, develop, and disseminate stages. However, after the define and design stages, this study only focuses on the development stage, namely the validity and practicality tests. The research instruments used were validation questionnaires and practicality questionnaires for teachers and students. The validity test was carried out by 5 expert teams and the practicality test was carried out on 8 teachers and 20 grade XI students. The results of the material and media validity test were obtained at 0.88 and 0.94 with a very valid category. The results of the e-module practicality test carried out by teachers and students were 90.38% and 95.74% with a very practical category. The results of the study show that a valid and practical PBL-based interactive acid-base e-module integrated with Canva has been produced for grade XI students.